Design, synthesis, and evaluation of novel O-alkyl ferulamide derivatives as multifunctional ligands for treating Alzheimer's disease. (31st December 2022) - Zhu, Gaofeng; Bai, Ping; Wang, Keren; Mi, Jing; Yang, Jing; Hu, Jiaqi; Ban, Yujuan; Xu, Ran; Chen, Rui; Wang, Changning; Tang, Lei; Sang, Zhipei
Abstract: Herein, a series of novel O -alkyl ferulamide derivatives were designed and synthesised through the multi-target-directed ligands (MTDLs) strategy. The biological activities in vitro showed that compounds 5a, 5d, 5e, 5f, and 5h indicated significantly selective MAO-B inhibitory potency (IC50 = 0.32, 0.56, 0.54, 0.73, and 0.86 μM, respectively) and moderate antioxidant activity. Moreover, compounds 5a, 5d, 5e, 5f, and 5h showed potent anti-inflammatory properties, remarkable effects on self-induced A β 1-42 aggregation, and potent neuroprotective effect on A β 1-42 -induced PC12 cell injury. Furthermore, compounds 5a, 5d, 5e, 5f, and 5h presented good blood–brain barrier permeation in vitro and drug-like properties. More interesting, the PET/CT images with [ 11 C]5f demonstrated that [ 11 C]5f could penetrate the BBB with a high brain uptake and exhibited good brain clearance kinetic property. Therefore, compound 5f would be a promising multi-functional agent for the treatment of AD. Graphical Abstract: UF0001